2010
DOI: 10.1002/etc.200
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐generational effects of polybrominated diphenylethers exposure: Embryonic exposure of male American kestrels (Falco sparverius) to DE‐71 alters reproductive success and behaviors

Abstract: Polybrominated diphenylethers (PBDEs) are additive flame-retardants that are environmentally persistent and bioaccumulative compounds of particular concern to species at high trophic levels, including predatory birds. The developmental effects of in ovo exposure to male birds at environmentally relevant levels of the PBDE technical mixture, DE-71, on reproductive success and behaviors using captive American kestrels (Falco sparverius) were determined. Males were exposed in ovo by direct maternal transfer to DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
(93 reference statements)
4
36
4
Order By: Relevance
“…They suggested that a lowest observed adverse effect level (LOAEL) for impaired pipping and hatching success could be as low as 1.8 mg/g egg wet weight [26]. Finally, Marteinson et al [27] examined the effect of embryonic exposure of DE-71 (a commercial PBDE mixture) on reproduction in male American kestrels via maternal transfer by feeding mothers. They reported lower reproductive success in pairs with high-exposed males, and female partners of high-exposed males laid smaller clutches, and produced smaller eggs with reduced fertility.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that a lowest observed adverse effect level (LOAEL) for impaired pipping and hatching success could be as low as 1.8 mg/g egg wet weight [26]. Finally, Marteinson et al [27] examined the effect of embryonic exposure of DE-71 (a commercial PBDE mixture) on reproduction in male American kestrels via maternal transfer by feeding mothers. They reported lower reproductive success in pairs with high-exposed males, and female partners of high-exposed males laid smaller clutches, and produced smaller eggs with reduced fertility.…”
Section: Discussionmentioning
confidence: 99%
“…A series of toxicity studies were conducted in which the American kestrel ( Falco sparverius ) was fed DE-71, after which reproduction and development endpoints were measured (Fernie et al 2008(Fernie et al , 2009Marteinson et al 2010Sullivan et al 2010 ). Adult American kestrels were exposed through their diet to control, 0.3, or 1.6 mg DE-71/kg (wm) for 75 days each year (Fernie et al 2008 ).…”
Section: American Kestrel ( Falco Sparverius )mentioning
confidence: 99%
“…In a further study, the reproductive success and behavior of male American kestrels exposed to DE-71 as embryos were assessed (Marteinson et al 2010 ). The F1 progeny of the F0 kestrels exposed via the diet (Fernie et al 2008 ) were never exposed directly via the diet, but only during the 28-days embryonic period via direct maternal transfer to the egg.…”
Section: American Kestrel ( Falco Sparverius )mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we analyzed as a PCB marker the 153 congener, which is both highly persistent and most often found at the highest concentration of PCB congeners in the blood of wild birds (Bustnes et al 2004;Helberg et al 2005). Polybrominated biphenyl ester (PBDE) congeners may deleteriously affect reproduction in raptors (Henny et al 2009;Johansson et al 2009;Marteinson et al 2010). We analyzed as a PBDE marker congener 47, found often in wild birds as the most abundant congener.…”
mentioning
confidence: 99%